Integrability in higher dimensions: A model with exact hopfion solutions - Babelon, O.; Ferreira, L. A. [UNESP] (Sissa Medialab Srl, 2002)
We review concepts of integrability in higher dimensions and apply them to construct Lorentz invariant field theories with an infinite number of local conserved currents.